Local Translation in Nervous System Pathologies - Gamarra, María; de la Cruz, Aida; Blanco-Urrejola, Maite; Baleriola, Jimena (Frontiers in Integrative Neuroscience, 2021)
Dendrites and axons can extend dozens to hundreds of centimeters away from the cell body so that a single neuron can sense and respond to thousands of stimuli. Thus, for an accurate function of dendrites and axons the neuronal proteome needs to be asymmetrically distributed within neurons. Protein asymmetry can be achieved by the transport of the protein itself or the transport of the mRNA that is then translated at target sites in neuronal processes. The latter transport mechanism implies that protein expression is achieved by translation of localized mRNAs. The role of local translation in nervous system (NS) development and maintenance is well established, but recently there is growing evidence that this mechanism and its deregulation are also relevant in NS pathologies, including neurodegenerative diseases. For instance, upon pathological signals disease-related proteins can be locally synthesized in dendrites and axons. Locally synthesized proteins can exert their effects at or close to the site of translation, or they can be delivered to distal compartments like the nucleus and induce transcriptional responses that lead to neurodegeneration, nerve regeneration and other cell-wide responses. Relevant key players in the process of local protein synthesis are the RNA binding proteins (RBPs), responsible for mRNA transport to neurites. Several neurological and neurodegenerative disorders, including amyotrophic lateral sclerosis or spinal motor atrophy, are characterized by mutations in genes encoding for RBPs and consequently mRNA localization and local translation are impaired. In other diseases changes in the local mRNA repertoire and altered local protein synthesis have been reported. In this review, we will discuss how deregulation of localized translation at different levels can contribute to the development and progression of nervous system pathologies.